Monetary anchor for East Asia: Japan or United States? - Quah, Chee-Heong.; Crowley, P.M.; Ismail, M.N. (Academic Journals, 2010)
In this paper we apply the optimum currency area (OCA) criteria to assess the suitability of whether the United States or Japan would best serve as monetary anchor country for East Asian countries. The criteria used are trade openness, business cycle synchronisation, exchange rate volatility, inflation convergence, and interest rate cycle synchronisation. The `performance' of these two potential monetary anchor countries is compared for three different economic periods: the pre-crisis, the crisis, and the post-crisis period. Based on ratings of 16 countries in the region, results suggest that the United States might be the more fitting candidate to be the anchor country.